The Role of Academy of Islamic Studies, University of Malaya, In Research On Plants and Herbs Mentioned in The Quran and Hadith - Mohd Yusoff, MY Zulkifli; Ahmad, Khadher; Othman, Rozana (Online Journal of Research in Islamic Studies, 2018)
Research is an important aspect that is emphasized in academia, especially for a Research University. Academy of Islamic Studies is one of the faculties in the University of Malaya, which is a Research University. To pave the way for achieving the goals of the university, the Academy of Islamic Studies conducts various researches in various fields in accordance to its primary field of Islamic studies. Based on descriptive and deductive analyses, this article aims to explain and investigate the role of the Academy of Islamic Studies, University of Malaya in conducting researches related to plants and herbs that are mentioned in the Quran and hadith of the Prophet SAW through the Transdisciplinary Research Grant Scheme (TRGS) entitled: ’Safe and Health Uses of Fruits and Herbs Mentioned in the Quran and Ahadith: An Analysis of Ethno medicinal Importance in Islamic Products in Malaysia’. From the investigations carried out, some aspects that are achieved in this research include: [1] Collecting and listing of plants and herbs that are mentioned in the Quran, followed by identification of verses and hadith, scientific names and benefits from scientific researches; [2] Establishing research collaborations between institutions or agencies from within and outside the country; [3] Organizing an international seminar and also participating as presenters for the purpose of sharing research outputs with various parties; [4] Publications in the form of books, journal articles, and working papers; and [5] Expert human capital development, in terms of candidates for the Doctor of Philosophy and Master’s degrees in Islamic Studies and Science.